2016
DOI: 10.1002/anie.201509864
|View full text |Cite
|
Sign up to set email alerts
|

Triazine‐Based Sequence‐Defined Polymers with Side‐Chain Diversity and Backbone–Backbone Interaction Motifs

Abstract: Sequence control in polymers, well‐known in nature, encodes structure and functionality. Here we introduce a new architecture, based on the nucleophilic aromatic substitution chemistry of cyanuric chloride, that creates a new class of sequence‐defined polymers dubbed TZPs. Proof of concept is demonstrated with two synthesized hexamers, having neutral and ionizable side chains. Molecular dynamics simulations show backbone–backbone interactions, including H‐bonding motifs and pi–pi interactions. This architectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 43 publications
1
88
0
1
Order By: Relevance
“…The obtained monodisperse oligomers, as well as the monomers, were carefully characterized by proton and carbon NMR, HRMS and HPLC. HPLC chromatograms and mass spectra thereby prove the high purity of the products …”
Section: Solid‐phase Synthesis Of Sequence‐defined Macromoleculesmentioning
confidence: 90%
See 3 more Smart Citations
“…The obtained monodisperse oligomers, as well as the monomers, were carefully characterized by proton and carbon NMR, HRMS and HPLC. HPLC chromatograms and mass spectra thereby prove the high purity of the products …”
Section: Solid‐phase Synthesis Of Sequence‐defined Macromoleculesmentioning
confidence: 90%
“…Due to this deactivation of the cyanuric chloride, which serves as a building block, the approach does not require any protecting groups. Different mono‐substituted cyanuric chloride submonomers were synthesized in a one‐step procedure in high yields (between 76 and 91%, depending on the substituent) and incorporated into the oligomeric backbone . By molecular dynamics simulations, it could be shown that triazine‐based polymers exhibit backbone interactions, such as π–π ‐interactions or hydrogen bonding.…”
Section: Solid‐phase Synthesis Of Sequence‐defined Macromoleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, valuable advances have been made in the field of sequence‐controlled polymerization. Iterative multi‐step approaches provide excellent sequence‐fidelity but are tedious to conduct and therefore limited to oligomers and smaller polymeric chains . Template‐based strategies, polymerizations based on multicomponent reactions, and the polymerization of sequence‐controlled precursors allow for higher molecular weights but are limited to relatively simple repetitive patterns.…”
Section: Methodsmentioning
confidence: 99%